Pelvic Compartments and Imaging Considerations Beyond TME Surgery for Rectal Cancer Patients - Majithia, Jinita; Baheti, Akshay D.; Haria, Purvi D.; Ankathi, Suman K.; Choudhari, Amit; Katdare, Aparna; Guha, Amrita; Unde, Himangi; Gala, Kunal; Shetty, Nitin S.; Kulkarni, Suyash; Kazi, Mufaddal (Journal of Gastrointestinal and Abdominal Radiology, 2025)
The rectum resides next to multiple important organs, muscles, nodes, nerves, and vessels. While operating in the mesorectal plane is sacrosanct for a successful rectal cancer surgery to obtain a negative circumferential resection margin and minimize local recurrence, advanced rectal tumors need to be operated beyond the standard surgical template. We discuss the various surgical options in such cases, and describe the imaging findings to consider helping the surgeon decide on the appropriate surgery.
Keywords: exenteration; rectal cancer; TME